Arrhythmogenic cardiomyopathy in children according to "Padua criteria": Single pediatric center experience. (1st March 2022) - Cicenia, Marianna; Cantarutti, Nicoletta; Adorisio, Rachele; Silvetti, Massimo Stefano; Secinaro, Aurelio; Ciancarella, Paolo; Di Mambro, Corrado; Magliozzi, Monia; Novelli, Antonio; Amodeo, Antonio; Baban, Anwar; Drago, Fabrizio
Abstract: Introduction: The aim of this study was to report clinical and arrhythmic features in a pediatric population affected by arrhythmogenic cardiomyopathy (ACM). Moreover, we assessed the concordance between the 2010 International Task Force criteria (ITF) and the 2020 Padua criteria. Methods: Inclusion criteria were "definite" or "borderline" ACM diagnosed according to the "Padua criteria" in patients <18 years old. History, electrocardiograms, ECG-holter monitorings, exercise testings, imaging investigations, electrophysiological studies, genetic testings and follow-up data were collected. Results: We enrolled 21 patients (mean age 13.9 ± 2 years). Most of them presented for minor arrhythmias. Premature ventricular complexes burden was 7.9 ± 10%. Cardiac magnetic resonance (19/21, 90.5% patients) showed right ventricular (RV) dilatation, wall motion abnormalities and late gadolinium enhancement (LGE) of both ventricles as predominant features [in 9 patients (52.9%) LGE left ventricle]. Genetic results (19/21 patient) showed compound heterozygous variants in 3/19 patients (15.8%), digenic in 3/19 (15.8%) and single in 6/19 (31.6%). Cardiac defibrillator (ICD) was indicated in 15 patients (71.4%): 6 in class I, 7 in class IIa, 2 in class IIb. Appropriate shocks occurred in 2 patients (13.3%), follow-up 5.46 ± 3.17 years According to 2010 ITF criteria: among the 18 patients with a "definite" ACM diagnosis, one patient would have had a "borderline" diagnosis, three a "possible" diagnosis and one no diagnosis and among the three patients with "borderline" diagnosis two would have had a "possible" diagnosis. Conclusions: Pediatric ACM can be diagnosed in the majority of cases secondary to incidental finding of simple ventricular arrhythmias. PVC burden is low and exercise induced arrhythmias rarely occur. Few patients with ICD experience appropriate shocks. "Padua criteria" improve the diagnostic accuracy. Highlights: Arrhythmic incidental finding is the initial manifestation for the majority of patients. Positive family history of arrhythmogenic cardiomyopathy/sudden cardiac death can help to identify the disorder Figure 1:, 2:, 3: and Supplementary Fig earlier. Investigate polymorphic and complexes premature ventricular contractions is extremely important. Most patients fulfill the indications for ICD implantation, but a minority experience arrhythmic events during follow-up. "Padua criteria" improve the diagnostic accuracy of the arrhythmogenic cardiomyopathy also in the pediatric setting.